The effects of addition of Zn, Sn, Mg, Cu, Fe, and Si on the morphology and corrosion behaviour of aluminium alloys in seawater - Ahmad A.; Yahya Z.; Daud N.A.Q.M.; Daud M. (2023)
In natural seawater, pure aluminum develops oxide layer which forms a barrier, protecting against corrosion. Alloying with other elements prevents the development of oxide layer by introducing localized galvanic cells. Different aluminum alloys exhibit different electrochemical behavior. The scope of the project was to study the effects of the addition of Zn, Sn, Mg, Cu, Fe, and Si on the morphology and corrosion behaviour in aluminium alloys. This is part of the work to study the electrochemical behaviour of aluminum alloys in natural seawater. The significance of understanding the corrosion behavior of aluminum alloys is essential in the fabrication of sacrificial anodes to be used in cathodic protection in corrosion control. Aluminum alloys were fabricated using alloying elements Zn, Sn, Mg, Cu, Fe, and Si. Divided into two groups, samples of aluminum alloys in Group 1 contain same weight percent of Zn, and different weight percent of Sn. Aluminum alloy samples in Group 2 contains same weight percent of Mg, Cu, Fe and Si with different weight percent of Sn. It was observed that the activeness of aluminum alloys also increases when alloyed with Zn, Sn, Mg, Cu, Fe, and Si. 2009 IEEE.